KERAGAAN FENOTIPIK BEBERAPA KLON KENTANG G1 TAHAN PENYAKIT LAYU BAKTERI - gunarto, anton (Jurnal Sains dan Teknologi Indonesia, 2009)
The purpose of the research is to investigate the phenotypic performances as qualitative of three potato clones resulted from protoplasm fusion (A5) and two clones from seeds(PAS3063 and PAS3064) which had been identified to be resistant to bacterial wilt disease (Ralstonia solanacearum). The commercial potato varieties (Granola and Atlantic)were used as a comparison varieties. All five varieties were produced from mini tuber G0. The result of qualitative performance that more prominent were on A5 clonewith the characters that the branch was red, tuber skin was purple/violet and it could produce the bloom. Meanwhile, the branch of another clone was green, tuber skin wasyellow/brown, and it could not produce the bloom, except PAS3064 clone and Atlantic even though it was not much. The color of fruit flesh was white except on Granola whichwas yellow. The result of cluster analysis that based on the character from each plant showed that PAS3064 was closed to Atlantic variety characteristic, PAS3063 was closed to Granola variety, and A5 different from both commercial varieties.